2015
DOI: 10.1016/j.ijcard.2014.11.161
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid prevents monocrotaline-induced pulmonary artery hypertension via inhibiting NLRP3 inflammasome activation in rats

Abstract: Ellagic acid ameliorates monocrotaline-induced pulmonary artery hypertension via exerting its anti-oxidative property inhibiting NLRP3 inflammasome signal pathway in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 38 publications
1
56
1
Order By: Relevance
“…3a) and caspase-1 (we analysed the active subunit p20) (Fig. 3b) were upregulated in MCT-treated pneumonectomised rats compared with the sham group, which is inconsistent with previous findings showing NLRP3 inflammasome activation during lung inflammation under the pathologic condition of PH in rats [7]. In PH rats, both treatment and pretreatment with A-740003 efficiently abolished the upregulation of P2X 7 R and greatly decreased the increase in caspase-1 and IL-1β (Fig.…”
Section: Resultscontrasting
confidence: 94%
See 1 more Smart Citation
“…3a) and caspase-1 (we analysed the active subunit p20) (Fig. 3b) were upregulated in MCT-treated pneumonectomised rats compared with the sham group, which is inconsistent with previous findings showing NLRP3 inflammasome activation during lung inflammation under the pathologic condition of PH in rats [7]. In PH rats, both treatment and pretreatment with A-740003 efficiently abolished the upregulation of P2X 7 R and greatly decreased the increase in caspase-1 and IL-1β (Fig.…”
Section: Resultscontrasting
confidence: 94%
“…Drugs targeting the prostacyclin, endothelin-1 receptor, and phosphodiesterase pathways improve symptoms and exercise tolerance, but persistent morbidity and mortality indicate that important pathogenic mechanisms are minimally affected [5, 6]. There is accumulating evidence of a specific contribution of NLRP3 and related inflammasomes, and their regulated cytokines or receptors may represent novel diagnostic or therapeutic targets in pulmonary diseases, including PAH [79]. …”
Section: Introductionmentioning
confidence: 99%
“…One such polyphenol is ellagic acid (EA) which is found in berries, grapes, pomegranates, and nuts. It has received increasing attention in the scientific community due its potential as an anti-inflammatory [26,27] and antioxidant [28][29][30] compound. A recent study has demonstrated that EA lowered blood pressure in hypertensive rats via an antioxidant effect of EA which includes increased nitric oxide synthase (NOS) expression and decreased ROS levels in the plasma [28].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the activation mode of NLRP3, inhibiting NLRP3 inflammasome activation may have beneficial effects in preventing the damage mediated by the sterile inflammatory response in cardiovascular diseases such as CHD and MI. Preventing pathological NLRP3 inflammasome from activation may provide some insight into the future prevention and treatment of cardiovascular diseases [1,3,10]. Currently, the most promising treatments for inhibiting NLRP3 are anti-IL-1, inhibition of caspase-1, and P2X7 receptors antagonist [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inflammasome is likely to control the inflammation in the development of cardiovascular diseases [6][7][8]. NLRP3 inflammasome, the most typically inflamma-some which could be activated by crystal or particle pathogen damage-associated molecular patterns (PAMPs) and ischemic hypoxia danger-associated molecular patterns (DAMPs), can promote the secretion of IL-1β and IL-18 [9][10][11]. Through these mechanisms, it promotes atherosclerosis (AS), coronary heart diseases (CHD), heart ischemia-reperfusion (I/R) injury, and so on [12].…”
Section: Introductionmentioning
confidence: 99%